Viral Escape from Dominant Simian Immunodeficiency Virus Epitope-Specific Cytotoxic T Lymphocytes in DNA-Vaccinated Rhesus Monkeys - Barouch, Dan H. (American Society for Microbiology, 2003)
Virus-specific cytotoxic T lymphocytes (CTL) are critical for control of human immunodeficiency virus type 1 replication. However, viral escape from CTL recognition can undermine this immune control. Here we demonstrate the high frequency and pattern of viral escape from dominant epitope-specific CTL in SIV gag DNA-vaccinated rhesus monkeys following a heterologous simian immunodeficiency virus (SIV) challenge. DNA-vaccinated monkeys exhibited initial effective control of the SIV challenge, but this early control was lost by serial breakthroughs of viral replication over a 3-year follow-up period. Increases in plasma viral RNA correlated temporally with declines of dominant SIV epitope-specific CD8(+) T-lymphocyte responses and the emergence of viral mutations that escaped recognition by dominant epitope-specific CTL. Viral escape from CTL occurred in a total of seven of nine vaccinated and control monkeys, including three animals that initially controlled viral replication to undetectable levels of plasma viral RNA. These data suggest that CTL exert selective pressure on viral replication and that viral escape from CTL may be a limitation of CTL-based AIDS vaccine strategies.